Konflik Batin dan Proses Pemulihan Diri Tokoh Utama dalam Film The Architecture Of Love: Kajian Psikoanalisis Sigmund Freud - Ramadhani, Tiara Annisa; Fidiyanti, Murni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the film The Architecture of Love using Sigmund Freud's psychoanalytic theory, which focuses on inner conflict and the process of self-recovery. The objectives of this study are to (1) describe the inner conflicts of the characters Raia and River based on the theory of the id, ego, and superego, and (2) describe the forms of self-recovery of the characters Raia and River after trauma. The theory used for analysis is Sigmund Freud's psychoanalytic theory. The method used is a qualitative descriptive method. The data sources were obtained from the film The Architecture of Love and secondary data sources, such as scientific journals. The research data consisted of film narratives related to the id, ego, super-ego, and the main characters' self-recovery process. The analysis techniques are (1) observing the film, (2) collecting data by recording behavioral phenomena that reflect the elements of the id, ego, superego, and the main characters' self-recovery process, (3) presenting the data and drawing conclusions. The results of this study show that there are four pieces of id data related to spontaneous emotions, desire for love, and closing oneself off from others. There are four ego data related to providing space for healing, doing productive things such as writing and drawing, and opening up again. There are two super ego data related to not easily opening one's heart before the trauma is gone and rediscovering life and new enthusiasm. There is also a form of self-recovery when both of them begin to open up to accept others, socialize, rediscover life, and find new enthusiasm. Keywords: Internal conflict, Self-healing, Sigmund Freud's psychoanalysis, Film The Architecture of Love